(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The aspiration of this study is to understand and analyze the concept of software Cloning and its detection. Software cloning is an acuity in which source code is duplicated. Software cloning and its detection is one of emerging and most dominant area of research in the field of software engineering. There exist numbers of techniques to detect clone in software. The focus of this study will be given on acquiring and analyzing the concept of hybrid clone detection technique. We will try to devise an algorithm for detecting duplicacy in the software by using hybrid software clone detection technique. The algorithm will first compute the required software metrics that provide sufficient information regarding the software application and then depending on software metrics matches the clone will be detected. While detecting clone we will focus on line clone rather than token or word.